Reality Monitoring and Feedback Control of Speech Production Are Related Through Self-Agency - Subramaniam, Karuna; Kothare, Hardik; Mizuiri, Danielle; Nagarajan, Srikantan S.; Houde, John F. (Frontiers in Human Neuroscience, 2018)
Self-agency is the experience of being the agent of one’s own thoughts and motor actions. The intact experience of self-agency is necessary for successful interactions with the outside world (i.e., reality monitoring) and for responding to sensory feedback of our motor actions (e.g. speech feedback control). Reality monitoring is the ability to distinguish internally self-generated information from outside reality (externally-derived information). In the present study, we examined the relationship of self-agency between lower-level speech feedback monitoring (i.e., monitoring what we hear ourselves say) and a higher-level cognitive reality monitoring task. In particular, we examined whether speech feedback monitoring and reality monitoring were driven by the capacity to experience self-agency—the ability to make reliable predictions about the outcomes of self-generated actions. During the reality monitoring task, subjects made judgments as to whether information was previously self-generated (self-agency judgments) or externally derived (external-agency judgments). During speech feedback monitoring, we assessed self-agency by altering environmental auditory feedback so that subjects listened to a perturbed version of their own speech. When subjects heard minimal perturbations in their auditory feedback while speaking, they made corrective responses, indicating that they judged the perturbations as errors in their speech output. We found that self-agency judgments in the reality-monitoring task were higher in people who had smaller corrective responses (p=.05) and smaller inter-trial variability (p=.03) during minimal pitch perturbations of their auditory feedback. These results provide support for a unitary process for the experience of self-agency governing low-level speech control and higher level reality monitoring.